2015
DOI: 10.1177/1074248415608011
|View full text |Cite
|
Sign up to set email alerts
|

Does Oral Beta-Blocker Therapy Improve Long-Term Survival in ST-Segment Elevation Myocardial Infarction With Preserved Systolic Function? A Meta-Analysis

Abstract: This meta-analysis demonstrates that oral beta-blocker therapy is associated with decreased all-cause mortality in patients with STEMI who are treated with primary PCI and who have preserved LVEF. This supports the current American College of Cardiology Foundation/American Heart Association 2013 Guideline for the Management of STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Such a high level will inevitably reduce inclusion rates but concerns of safety have been raised for selecting the lower level of ≥40%. In a recent meta-analysis of PCI-treated patients with STEMI and preserved LVEF, however, Misumida et al 31 found no differences in a favorable mortality outcome of β-blockers versus no β-blockers in a subgroup analysis stratified according to the definition of LVEF being >40% or >50%. In a large recent UK registry study 15 , where patients with a diagnosis of heart failure had been carefully excluded, no differences in lack of mortality reduction were found among patients with LVEF ≥50% versus all patients who had LVEF measured, with a cut-off level of ≥30%.…”
Section: Discussionmentioning
confidence: 96%
“…Such a high level will inevitably reduce inclusion rates but concerns of safety have been raised for selecting the lower level of ≥40%. In a recent meta-analysis of PCI-treated patients with STEMI and preserved LVEF, however, Misumida et al 31 found no differences in a favorable mortality outcome of β-blockers versus no β-blockers in a subgroup analysis stratified according to the definition of LVEF being >40% or >50%. In a large recent UK registry study 15 , where patients with a diagnosis of heart failure had been carefully excluded, no differences in lack of mortality reduction were found among patients with LVEF ≥50% versus all patients who had LVEF measured, with a cut-off level of ≥30%.…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, the population was unselected, consecutive, and prospectively included. Interestingly, the proportion of patients with reduced LVEF was nearly half that in the large North-American ACTION registry [6], even when patients with a history of heart failure had been excluded (19.8% with a reduced LVEF). Beyond a large difference in the number of study participants, 16% of patients in the ACTION registry presented with heart failure or shock.…”
Section: Discussionmentioning
confidence: 99%
“…The only randomized post-AMI trial using LVEF for inclusion was CAPRICORN where all had LVEF < 40%. A recent meta-analysis by Misumida et al [6] included 7 trials of patients treated with primary PCI for ST elevation AMI without a reduced LVEF. There were no differences in combined hazard ratios for death with β-blocker versus non-β-blocker according to studies with cut-off points for LVEF >40% (n = 3) versus LVEF > 50% (n = 4).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of seven observational studies, oral beta-blocker therapy was associated with decreased all-cause mortality in patients with STEMI who were treated with primary PCI and had a preserved ejection fraction [23]. In a post-hoc analysis of the CHARISMA trial, the use of beta-blockers in patients with prior MI but no heart failure was associated with a lower composite cardiovascular outcome driven by lower risk of recurrent MI with no difference in mortality [24].…”
Section: Beta Blockersmentioning
confidence: 98%